2018
DOI: 10.21608/sjfop.2018.31467
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tuberose Plants (Polianthes Tuberosa L.) to Chemical and Bio Fertilization and Their Effect on Vegetative Growth, Flowering and Chemical Composition Under Sandy Soil Conditions

Abstract: to study the effect of partial substitution of chemical nitrogen fertilizer with biofertilizer containing two strains of nitrogen-fixing (Azospirillum lipoferum, Azotobacter chrococcoum), on vegetative growth, flowering and chemical composition of tuberose plants (Polianthes tuberosa L.) under sandy soil conditions to rationalize the use of mineral fertilizers and reduce pollution of the environment in order to increase the quantity and improvement quality of the product on the tuberose plants during the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The role of biofertilizer in improving N, P and K %, which is in harmony with the obtained results was revealed by Mazhar and Eid (2016) and Sathyanarayana et al (2018) on gladiolus, Fawzy et al (2012) on onion, Parmar et al (2017) on golden rod, Attia et al (2018) on tuberose. Also, vitamin E increased N, P and K % as reported by Abdou et al (2012Abdou et al ( , 2013aAbdou et al ( and 2013b) on mint, caraway and guar plants, respectively, and Mohamed (2016) on Antirrhinum majus plant.…”
Section: Chemical Constituents: a Photosynthetic Pigmentssupporting
confidence: 88%
“…The role of biofertilizer in improving N, P and K %, which is in harmony with the obtained results was revealed by Mazhar and Eid (2016) and Sathyanarayana et al (2018) on gladiolus, Fawzy et al (2012) on onion, Parmar et al (2017) on golden rod, Attia et al (2018) on tuberose. Also, vitamin E increased N, P and K % as reported by Abdou et al (2012Abdou et al ( , 2013aAbdou et al ( and 2013b) on mint, caraway and guar plants, respectively, and Mohamed (2016) on Antirrhinum majus plant.…”
Section: Chemical Constituents: a Photosynthetic Pigmentssupporting
confidence: 88%
“…The role of Microbein biofertilizer (M.B.) in improving vegetative growth and flowering parameters was revealed by Dalve et al (2009), Kaushik et al (2016), Zehra et al (2017), Sathyanarayana et al (2018) and Bohra and Nautiyal (2019) on gladiolus, Kumar et al (2012), Attia et al (2018) and Avinash et al (2019) on tuberose, Fayaz et al (2018) on tulip plant. The role of ascorbic acid (vit.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors evaluated the effect of biofertilizer such as, El-Sayed (2004), Taha and Hassan (2008), Abdou and Ibrahim (2015), Mazhar and Eid (2016), Sathyanarayana et al (2018) and Hassan and Abd El-Azeim (2020) on gladiolus and Attia et al, (2018) on tuberose plants. Hassan (2016) on gladiolus and Afifpour and Kosh-Khui (2015) on Polianthes tuberosa found that amino acids have positive effect on N, P and K %.…”
Section: N P and K %mentioning
confidence: 99%